Whole blood viscosity of preterm infants: differences to term neonates - Kuß, Navina; Bauknecht, Elisa; Schmidt, Claudia; Gehm, J.; Gehm, L.; Pöschl, Johannes; Ruef, Peter (Clinical hemorheology and microcirculation, 2015)
Determination of shear stresses at given shear rates with the LS 300 allows approximation of flow curves by mathematical models and to calculate viscosities of non-Newtonian fluids across the entire physiological shear range. Particular in preterm ne
Die angegebene DOI funktioniert nicht
Gesehen am 03.06.2020